Development of precision force sensor with specified measuring range - Li, Lei (2010)
In this report, a compliant-mechanisms-based precision force sensor has been developed. The first part of the report is devoted to the mechanism design of the force sensor. The compliant mechanism is chosen due to its nano-motion ability, compactness, ease of manufacturing, reduction in wear and lubrication, etc. In order to improve the sensor’s accuracy, high linearity of stiffness is preferred. As a result, compound linear spring mechanism based on the compliant structure is investigated and used as it exhibits high linear stiffness properties. The second effort has been made to establish the analytical model for the flexible beam in the compliant structure to investigate the linearity of beam’s stiffness. The analytical model is built based on the method of elliptic integral. Numerical model based on the finite element method has also been carried out to analyze the linearity of flexible beam’s stiffness since it is much easier to use and can handle more complex situations compared to the analytical model.